Feasibility Study of Concrete Louvers for High-rise Residential Buildings in Terms of Cooling Energy Requirements - Bahaadin, Sara Dh.; Raof, Binaee Y.; Abdulrahman, Hendren (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
High-rise residential buildings are increasing worldwide, including cities in the Kurdistan Region of Iraq. Therefore, creating sustainable environments in and around these residential buildings are becoming an important problem. Improving energy efficiency in buildings has received critical attention worldwide. Countries have developed national sustainability strategies that lead to the lower energy consumption while maintaining comfort, reducing energy consumption, and minimizing harmful emissions. In this paper, an analysis of the impact of external shading devices in high-rise residential buildings on energy consumption of a 13-storey building in Sulaimani city is studied. The study is focused on fixed shading elements, explaining the influence of the design of vertical and horizontal shading devices on the total energy consumption of this type of building. The results show that both a single fixed horizontal blind with a depth of 20 cm and a triple vertical shading with the same depth are considered useless. The reduction in cooling loads by two fixed horizontal louvers almost doubled compared to a single fixed horizontal shading with 20 cm. Moreover, triple fixed horizontal louvers with 40 cm have almost the same effect on reducing cooling loads as triple fixed louvers with 60 cm. On the other hand, a triple fixed horizontal shading device with 60 cm has twice the effect on reducing annual cooling loads as a triple fixed vertical shading device with 60 cm.